2018
DOI: 10.2147/ceor.s169045
|View full text |Cite
|
Sign up to set email alerts
|

Cost-minimization analysis of degludec/liraglutide versus glargine/aspart: economic implications of the DUAL VII study outcomes

Abstract: BackgroundDiabetes represents a relevant public health problem worldwide due to its increasing prevalence and socioeconomic burden. There is no doubt that tight glycemic control reduces the development of diabetic complications such as the long-term costs related to the disease. The aim of our model was to calculate total direct costs associated with the two treatments considered in DUAL VII study, and hence evaluate the potential economic benefits for the National Health System (NHS) deriving from the use of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Although no other economic analyses have been found comparing these therapeutic options, results shown in our study are comparable with those of other economic evaluations conducted on different antidiabetic drugs fixed combinations. 57-62 In various studies in the literature, it is shown that the high cost of the newer drugs is offset by the benefits obtainable on the reduction of complications, especially cardiovascular events and hypoglycemia. Our cost-utility allows us to go beyond the pure analysis of costs and provides a global assessment of the therapy’s value, highlighting the potential economic benefits for the NHS, due to the enhancement of multiple clinical outcomes in patients with diabetes and improvement of the quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Although no other economic analyses have been found comparing these therapeutic options, results shown in our study are comparable with those of other economic evaluations conducted on different antidiabetic drugs fixed combinations. 57-62 In various studies in the literature, it is shown that the high cost of the newer drugs is offset by the benefits obtainable on the reduction of complications, especially cardiovascular events and hypoglycemia. Our cost-utility allows us to go beyond the pure analysis of costs and provides a global assessment of the therapy’s value, highlighting the potential economic benefits for the NHS, due to the enhancement of multiple clinical outcomes in patients with diabetes and improvement of the quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…No prior economic evaluations of IDegLira versus iGlarLixi have been conducted for Italy but IDegLira was recently compared with basal-bolus insulin in a cost-minimization analysis, based on the DUAL VII trial 40. The analysis showed that IDegLira was associated with higher acquisition costs which were partially offset by reduced needle, SMBG testing and hypoglycemia costs.…”
Section: Discussionmentioning
confidence: 99%
“…When lower IDegLira doses were used, IDegLira was cost saving relative to basal-bolus therapy. From the perspective of the Italian NHS, IDegLira was considered to offer an important alternative to basal-bolus insulin therapy 40. To date, one other cost-effectiveness analysis comparing IDegLira with iGlarLixi has been published.…”
Section: Discussionmentioning
confidence: 99%
“…Direct and indirect medical costs were calculated and then reported in Egyptian pounds in 2018. CMA was conducted using Microsoft Excel ® to determine the difference in the treatment costs between both regimens …”
Section: Methodsmentioning
confidence: 99%